Legal Analysis of the Cancellation of Homologation in the Process of Postponement of Debt Payment Obligations (PKPU) in Decision Number 1345 K/Pdt.Sus-Bankment/2024 - Iwan Hermawan; Radian Syam (Sean Institute, 2026)
Suspension of Debt Payment Obligations (PKPU) is a legal mechanism that provides debtors with the opportunity to restructure their debts through a peace agreement with creditors. The peace agreement becomes legally binding after being ratified by the court through homologation. However, Law Number 37 of 2004 allows for the cancellation of homologation if the debtor fails to implement the terms of the peace agreement, which can lead to bankruptcy and significant legal consequences for the parties. This problem is reflected in Decision Number 1345 K/ Pdt.Sus -Pailit/2024, so it needs to be studied in depth. The formulation of the problem in this study includes: first, how the judge's legal considerations in deciding to cancel the homologation in Decision Number 1345 K/ Pdt.Sus -Pailit/2024 and second, what are the legal consequences of the cancellation of homologation for debtors and creditors in the decision. The research method used is normative juridical legal research with a statutory approach, a case approach, and a conceptual approach. The legal materials used consist of primary, secondary and tertiary legal materials which are analyzed qualitatively. The results of the study indicate that the judge's legal considerations in deciding the cancellation of homologation are based on the proven negligence of the debtor in carrying out payment obligations as stipulated in the homologated peace agreement , thus fulfilling the provisions for homologation cancellation according to Law Number 37 of 2004. Viewed from the theory of legal certainty, justice, and benefit, the decision confirms the consistency of the application of the law to violations of peace. The legal consequences of the cancellation of homologation in the a quo decision are the termination of the PKPU peace agreement, the change in the debtor's legal status to bankruptcy, and the restoration of the creditor's rights to collect their receivables through the bankruptcy mechanism according to the principle of paritas creditorum .